A Soulful Approach to Dissociation Resulting From Trauma. (27th March 2018) - Simington, Jane
Abstract : Intrusive Symptoms, including dissociation, are experienced by many of the millions who suffer from Posttraumatic Stress Disorder (PTSD). Dissociation involves a disconnection from the overwhelming emotional content of the traumatic experience, with reactions ranging from brief moments of detachment to complete neurological collapse. The disappointing clinical results in cognitive- behavioral exposure-based therapies have stimulated interest in wholistic methods that addresses the spiritual needs of those who experience trauma symptoms. This paper reviews the research literature suggesting an inverse correlation between spirituality-focused interventions and PTSD symptomology, and provides a neurological and soulful comparison of dissociative symptoms and the application for clinical practice.